2016
DOI: 10.18203/2394-6040.ijcmph20160925
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study on mental health status of pregnant women at urban health centre of Bangalore, India

Abstract: Background: Depressive disorders are a common source of disability among women. In addition to the economic and human costs of maternal depression, children of depressed mothers are at risk for health, developmental, and behavioural problems. Community-based epidemiological data on antenatal depression from developing countries is scarce. Methods: A cross sectional study was carried out for a period of 4 months in urban health centre in Bangalore. Simple random sampling technique was used to select 250 pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 4 publications
4
9
0
Order By: Relevance
“…This difference was found to be statistically significant. Similar results were also obtained by a study conducted by Maheshwari et al, while contra results were seen in another study by Kumar et al 14,17…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This difference was found to be statistically significant. Similar results were also obtained by a study conducted by Maheshwari et al, while contra results were seen in another study by Kumar et al 14,17…”
Section: Discussionsupporting
confidence: 90%
“…Similar prevalence of depression was seen in other studies, 18%, 24.8%, 26%, while a few others showed a higher prevalence of depression 35.7%, 36.76%, suggesting that this is a need to screen the antenatal women for early diagnosis and effective management of depression. 4,11,[14][15][16] In Table 1 which depicts the socio-economic factors associated with depression it is seen that most of the women were Hindu, 67.6%, followed by Muslims 29.5%. Majority of the women were in the age group 18-25 years (63.5%), suggesting a still prevalent tradition of early marriages and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though maximum number of women enjoyed fair relationship with their In laws, there was statistically significant (P=0.0037) presence of depression in pregnant women who had bad relation with in law. It was found that 26 % patients had EPDS score of 10 0r more indicating depression which was comparable to study conducted by Maheshwari M, et al (2016) 6 . Majority of women with EPDS score >10 were in the age group above 30 years and in 3 rd trimester of pregnancy.…”
Section: Resultssupporting
confidence: 78%
“…Our study found that poor social relations In-laws were strongly related with depression among pregnant women, as has been found in other studies as well. 6,10 …”
Section: Resultsmentioning
confidence: 99%